AKULTURASI HUKUM ISLAM DAN ADAT DALAM TRADISI BAPAPAI DALAM PERNIKAHAN ADAT BANJAR DI KECAMATAN BETARA KABUPATEN TANJUNG JABUNG BARAT - Rusma Wati; Ahmad Syukri; Ramlah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Bapapai tradition is a wedding bathing ritual of the Banjar tribe in Betara District that symbolizes physical and spiritual purification before marriage. The existence of this ritual contains syncretism between pre-Islamic beliefs and Islamic values, prompting the need to examine the form of acculturation between Islamic law and customs in its practice. This study aims to analyze the process, transformation of meaning, and the position of the Bapapai tradition from the perspective of Islamic law. The research method used is qualitative with a socio-legal and ethnographic approach. Data were collected through in-depth interviews, observation, and documentation in Betara District, then analyzed using the Maqashid Syariah lens. The results show that Bapapai functions as a rite of passage and a symbol of prayer for household blessings. A transformation of meaning has occurred from mystical to religious practice, where pre-Islamic elements such as offerings have been adapted with prayers, salawat, and zikir. From the Maqashid Syariah perspective, this tradition is categorized as 'Urf Shahih (valid custom) and an aspect of Tahsiniyat (perfection of aesthetics and ethics) as it supports mental health and does not conflict with sharia as long as it remains free from shirk and maintains modesty. The conclusion confirms that the Bapapai tradition in Betara District is a form of harmonious acculturation that integrates Islamic values into local culture without losing the ancestral identity of the Banjar tribe.